Antioxidant Activity Of Hydrolyzed Black Soybean (Glycine Soja Linn. Sieb.) By β-Carotene Bleaching - Masdiana Tahir; Zainal Abidin; Nilla Sukmawati (Jurnal Farmasi dan Ilmu Pengobatan, 2017)
Black soybean (Glycine soja Linn. Sieb.) contain flavonoid compounds known as isoflavones. Isoflavones are kind of flavonoid which is the highest antioxidative activity exhibited by the isoflavones aglycones, especially genistein. Isoflavone glycosides containt in G. soja can be hydrolyzed to be aglycone (genistein) using an acid. The aim if this research was to investigate the antioxidant activity of the hydrolyzed G. soja extract that was obtained by β-carotene bleaching method. The result showed that the hydrolyzed G. soja extract has the value of antioxidant activity 42.8% and 81.1% for the standards solution of quercetin. Therefore, it can conclude that the hydrolyzed G. soja extract has the efficacy as an antioxidant.